MNGI-03. PATIENT PARAMETERS ASSOCIATED WITH TUMOR GROWTH IN INCIDENTAL MENINGIOMA. (5th November 2018) - Kamson, David; Yuen, Carlen; Castillo-Saavedra, Laura; Wilmington, Andrew; Walker, Matthew; Merrell, Ryan
Abstract: BACKGROUND: Meningiomas are the most common primary intracranial tumors. Obesity or nulliparity are established risk factors for the development of these tumors. While radiographic tumor characteristics have been shown to be predictive of future tumor growth as demonstrated by the Asan Intracranial Meningioma Scoring System (AIMSS) [1], the relation of patient characteristics with tumor growth has been largely unexplored. The present study aims to evaluate a set of patient characteristics for predicting tumor growth and to assess whether these may provide information in addition to radiographic data for the prediction of progression free survival (PFS). METHODS: Ninety-two treatment-naïve patients with incidental meningiomas (mean±SD age 62 ± 14y; 73F) were enrolled with at least 2 contrast-enhanced MRIs acquired in a state ≥0.5y apart (mean: 4.3 MRIs/patient; mean follow-up time 4.5 ± 3.8y). Age, height, BMI, sex were recorded for all patient, and parity available for 32 patients. Two-dimensional tumor growth rate(TGR, mm 2 /mo) calculated for all patients, while the AIMSS score was recorded for 81 patients. PFS was established as per the RANO criteria, defining progression as ≥25% increase in size. RESULTS: Age had a weak positive (r=0.21), while height had a weak inverse correlation (r=-0.19) with TGR (p CONCLUSION: Our preliminary data suggests that population data such as age, sex, height and BMI may have a value independent of radiographic characteristics to predict progression in incidental meningioma. Of these parameters, BMI is a modifiable risk factor. Weight loss could be evaluated as a potential intervention to slow down meningioma growth. [1] Lee, EJ, et al. Journal of neurosurgery 127.5 (2017): 971–980.